BUILDING SOLIDARITY VALUES BETWEEN IMMIGRANT COMMUNITIES WITH LOCAL COMMUNITIES IN STRENGTHENING NATIONAL INTEGRATION (Community Study in Rumak Village, Kediri Regency, West Lombok Regency) - Muh Mabrur Haslan; Dahlan Dahlan (Jurusan P. IPS, FKIP, Universitas Mataram, 2020)
AbstractThe purpose of this study is: (1) to find understanding to build values solidarity between immigrant community with local community in strengthen national integration at community in Rumak Village Kediri District West Lombok Regency (2) to find understanding supplementary and inhibition factor to build values solidarity between immigrant community with local community in strengthen national integration at community in Rumak Village Kediri District West Lombok Regency.The method of research use kualitatif approach with description method. Meanwhile the technique in collecting the data is in-depth interview, obervation, and documentation. Furthermore data analysis conducted completely during data collection in very focus of activities and every finishing data collection. The result of research such as: (1) to build values solidarity between immigrant community with local community in strengthen national integration at community in Rumak Village Kediri District West Lombok Regency, such as: mutual cooperation, repeated recitation of the confession of faith, belangar, betalet or betuqa, pilgrimage, and bicycle sport (2) to find understanding supplementary and inhibition factor to build values solidarity between immigrant community with local community in strengthen national integration at community in Rumak Village Kediri District West Lombok Regency, such as: communication and good social relation between immigrant community with local community. Relation approach between immigrant community with local community is part of important from supplementary factor to build social solidarity. Inhibition factor to build values solidarity in strengthen national integration are community to have pragmatics life style, hedonism and materialisticly. AbstrakPenelitian ini bertujuan untuk mengetahui (1) upaya untuk membangun nilai-nilai solidaritas antara masyarakat pendatang dengan masyarakat lokal dalam memperkuat integrasi nasional pada masyarakat di Desa Rumak Kecamatan Kediri Kabupaten Lombok Barat (2) faktor-faktor pendukung dan penghambat dalam memperkuat integrasi nasional pada masyarakat di Desa Rumak Kecamatan Kediri Kabupaten Lombok Barat. Pendekatan penelitian ini menggunakan pendekatan kualitatif dengan metode diskriptif. Teknik pengumpulan data dengan menggunakan tekinik wawancara , observasi dan dokumentasi. Selanjutnya analisa data dilakukan pada saat pengumpulan data yang dilakukan secara menyeluruh. Hasil penelitian ini adalah (1) Upaya membangun nilai-nilai solidaritas antara masyarakat pendatang dengan masyarakat lokal dalam memperkuat integrasi nasional adalah: gotong royong, kegiatan tahlilan, belangar, betalet atau betuqa, ziarah haji dan kegiatan olahraga sepeda santai. (2) Faktor pendukung dalam membangun nilai-nilai solidaritas antara masyarakat pendatang dengan masyarakat lokal dalam memperkuat integrasi nasional adalah adanya komunikasi dan relasi sosial yang baik antara masyarakat lokal dengan masyarakat pendatang. Sedangkan faktor penghambat adalah masyarakat cenderung mempunyai gaya hidup yang pragmatisme, hedonis dan materialis.